The Use of Adipose-Derived Stem Cells in Cell Assisted Lipotransfer as Potential Regenerative Therapy in Breast Reconstruction - Kamayana, Jenisa Amanda Sandiarini (Scripta Medica, 2022)
Breast reconstruction for breast cancer patients is performed as a standard of care to improve patients’ quality of life, physical and psychosocial well-being. Stem cell therapy holds a promise in regenerative medicine, including in breast reconstruction. This review explores the potential use of adipose-derived stemcells (ADSCs) in cell assisted lipotransfer (CAL) for reconstruction of the breast. Adipose-derived stem cells are multipotent cells with angiogenic and immunomodulatory potential. Several studies reveal ADSCs use in CAL results in long-term breast volume retention suggesting improved fat graft survival. Some conflicting outcomes are also discussed, potentially related to numbers of cells enriched and factors affecting the cells’ microenvironment. The use of ADSCs in CAL may be beneficial for therapy of breast reconstruction in breast cancer patients after surgical management. Further investigation would be needed to improve the confidence of its clinical use.
Keywords: Adipose-derived stem cell; breast reconstruction; breast surgery; regenerative therapy; cell assisted lipotransfer; fat graft; stem cell therapy